2019
DOI: 10.3390/tropicalmed4020083
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Public Preferences, Priorities, and Policy Perspectives for Controlling Invasive Mosquito Species in Greece

Abstract: Climate change, urbanization, and financial crisis have created a dramatic mixture of challenges in Southern Europe, increasing further the risks of transmission of new vector-borne diseases. In the last decade, there has been a wide spread of an invasive mosquito species Aedes albopictus, commonly known as the Asian tiger mosquito, in various urban ecosystems of Greece accompanied by greater risks of infectious diseases, higher nuisance levels, and increased expenses incurred for their control. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nowadays, the only invasive mosquito species (IMS) that is present in Greece is Ae. albopictus and its establishment may cause problems for public health [ 9 , 10 , 11 ]. Therefore, a management plan to control Ae .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the only invasive mosquito species (IMS) that is present in Greece is Ae. albopictus and its establishment may cause problems for public health [ 9 , 10 , 11 ]. Therefore, a management plan to control Ae .…”
Section: Introductionmentioning
confidence: 99%
“…albopictus in a certain area [ 25 , 28 , 35 ]. Previous studies showed that Aedes albopictus presence is higher in urban areas of the Region of Attica [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial action to start an effective and sustainable mosquito control program is the establishment of a mosquito management board able to identify the most appropriate mosquito surveillance and control objectives according to the social and political context, the available human and material resources and the local entomological and epidemiological scenario. Ideally, a cost-benefit analysis on the mosquito management program should be conducted by independent experts to evaluate the convenience of implementing the program [ 26 ].…”
Section: Obstacles and Challenges Of Qa And Qc Programsmentioning
confidence: 99%